Thyroid secondary cancer (Primary: hypernephroma) - Estrugo, Roberto; Toledo, Nancy; dos Santos, Gustavo (Cirugía del Uruguay, 1985)
. Description of I series of 7 cases of secondary thy• roid cancer the origin of which corresponds to renal adenocarcinoma. Discussion of its cli)ical presentation as thyroid nodules with macro and microscopy, in every aspee!, equal to those of the primary tumor. In respect of the therapeutic action, agressive remo• val is indicated, discussing different possibilities. Emphasis is laid on frequency of these tumours, superior to frequency of primary cncers of the thyroid in the necropsic series.